Assessing the Role of Antioxidants in Migraine Patients in Erbil City - Lana Othman Mahmood; Kamaran Abdoulrahman (College of Pharmacy University of Baghdad, 2024)
Migraine is a prevalent chronic condition that is often characterized by recurrent incapacitating headache attacks and related symptoms. The purpose of this investigation was to assess the potential effects of antioxidants on migraine disease. The main goal of the study was to measure the concentrations of many important antioxidants, such as catalase (CAT), superoxide dismutase (SOD), thioredoxin (TRX), and glutathione peroxidase 1 (GPX1). Ninety participants were recruited from the outpatient headache clinic of the neurology department at Al Jumhury Teaching Hospital in Erbil City for this study. In this study, there were 60 patients with migraine and 30 controls. Among the migraine group, there were 45 female and 15 male participants, while the control group consisted of 20 female and 10 male participants, with matching in terms of age and sex. According to study results, both male and female migraine patients had significantly lower levels of enzymes SOD and GPX1 compared to the control group. Additionally, female migraine patients had lower levels of CAT significantly compared to the control group. In male migraine patients, CAT also showed lower levels, but the difference was not statistically significant. On the other hand, TRX showed lower levels in both female and male migraine patients, but the difference was not statistically significant compared to the control group. There was a negative correlation observed between the frequency of headache-related days per month and the serum concentrations of SOD. This implies that as the levels of SOD in the serum decrease, the number of headache-related days per month tends to increase.